2019
DOI: 10.1108/ijsi-03-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-based fatigue life of vehicle spring under random loading

Abstract: Purpose The purpose of this paper is to analyse fatigue-life prediction based on a reliability assessment for coil springs of vehicle suspension systems using different road excitations under random loading. Design/methodology/approach In this study, a reliability assessment was conducted to predict the fatigue life of an automobile coil spring during different road data surfaces. Campus, urban and highway road surfaces were considered to capture fatigue load strain histories using a data acquisition system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Reliability assessment of the fatigue life is vital for safe operation (Manouchehrynia et al, 2019). The probabilistic nature of fatigue failure refers to the random fatigue life of a set of specimens with nominally identical geometry and dimensions subjected to cyclic loading…”
Section: Fatigue Life Prediction Of Emu Gearmentioning
confidence: 99%
“…Reliability assessment of the fatigue life is vital for safe operation (Manouchehrynia et al, 2019). The probabilistic nature of fatigue failure refers to the random fatigue life of a set of specimens with nominally identical geometry and dimensions subjected to cyclic loading…”
Section: Fatigue Life Prediction Of Emu Gearmentioning
confidence: 99%
“…The rotor bracket, poles, yoke, and shaft are the core components of rotor components. Among them, the force of the rotor bracket is the most complicated [27][28][29]. Therefore, the rotor support with the fixed rotating shaft, magnetic yoke, and magnetic pole is the object of engineering research in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are several ways to predict the fatigue life. Nya et al 17 established the concept of fatigue reliability as a system of correlated events during service life to predict the probability of fatigue life using Coffin–Manson, Morrow and SWT models. Rajadurai et al 18 observed that composite wind turbine blades failed due to matrix compression and proposed a new set of failure criteria to predict the failure of composite wind turbine blades, which can predict the maximum shear stress region in transverse compression.…”
Section: Introductionmentioning
confidence: 99%